A Summary of the Second Annual HIV Microbiome Workshop - Williams, Brett (AIDS Res Hum Retroviruses, 2017)
Commensal organisms appear to play significant roles in normal homeostasis as well as in the pathogenesis of HIV infection in a number of different organ systems. On November 17th and 18th, 2016, leading researchers from around the world met to discuss their insights on advances in our understanding of HIV and the microbiome at the National Institutes of Health (NIH) in Bethesda. Dr. Elhanan Borenstein of the University of Washington gave a keynote address where he discussed new developments in systems biology which hold the promise of illuminating the pathways by which these organisms interact with human physiology. He suggested that we need to get past correlations in microbiome research by using models and informatics which incorporate metagenomics to predict functional changes in the microbiome.